Preparation and characterization of microalgal oil loaded alginate/poly (vinyl alcohol) electrosprayed nanoparticles - Inan, Benan; Ozcimen, Didem (ELSEVIER, 2021)
Microalgae contain many bioactive compounds which are attractive as research targets for nutraceutical and pharmaceutical applications due to their potential therapeutic activities. Many of these compounds have antioxidant, antiviral, antibacterial, antifungal, anti-inflammatory, antitumor characteristics. Utilizing microalgal compounds with nanotechnological approaches to improve the physical and chemical stability are relatively new, and it is promising to apply these for both food supplements and pharmaceutical purposes. In this study, nanoparticle production using microalgal oil extracts were performed by electrospraying via using polyvinyl alcohol (PVA) and alginate as biopolymeric wall. The effect of different polymer solution, flow rate and collector distance on particle size of nanoparticles were also investigated statistically, and the processes were modelled. Nanoparticles were obtained with the size of 90 nm, and the optimum electrospraying conditions were found to be 8% PVA solution, flow rate of 0.2 ml/h and 13 cm collector distance. Characterization studies, release and stability tests showed the structure of the nanoparticle, its resistance to the environmental conditions and release profile of the nanoparticles. The encapsulation efficiency was found to be in the range of 60-70% for nanoparticles. Antibacterial activity of nanoparticles showed that the strongest antibacterial activity was determined against Escherichia coli ATCC 8739, with the inhibition zone of 12-14 mm for nanoparticles loaded with Botryococcus braunii and Microcystis aeruginosa oil, respectively. The DPPH antioxidant assay results showed that nanoparticle structure are effective in protecting the algal bioactive compounds and can be useful for future pharmaceutical and food applications. (C) 2021 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Bioactives; Electrospraying; Microalgae; Nanoparticle; Antibacterial activity; BIOACTIVE COMPOUNDS; FABRICATION; NANOFIBERS; ENCAPSULATION; Biotechnology & Applied Microbiology; Engineering; Food Science & Technology